Naive Linguistics on the Internet and the Transformation of Communicative Norms in Educational Discourse - Ismoilova, Ra’no (The Lingua Spectrum, 2025)
The article analyzes the phenomenon of naïve linguistics emerging in the internet environment and its impact on the transformation of communicative norms within modern educational discourse. The mechanisms of forming everyday linguistic beliefs, features of digital communication, and changes in students’ speech culture influenced by online interaction are examined. The role of the educator as a mediator between scientific and naïve linguistic knowledge is highlighted. The necessity of developing medialinguistic competence and fostering responsible communicative behavior is emphasized.